Differences in Dietary Density Between Physical Activity Group and Tele-nutrition Counseling with Physical Activity Group - Prasetyo, Teguh Jati; Putri, Winda Alisa; Khoiriani, Izzati Nur; Listiandi, Arfin Deri; Surijati, Katri Andini; Rahmah, Hiya Alfi; Sulistyaning, Afina Rachma; Wicaksari, Sifa Aulia; Ramadhan, Gumintang Ratna (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
Obesity is one of the risk factors for non-communicable diseases. Lifestyle changes such as physical activity and improved diet through tele-nutrition counseling are effective ways to overcome obesity. The study aims to determine the difference in dietary density in the group given physical activity and tele-nutrition counseling with the group physical activity in obese adults. Quasy-experimental research design with the untreated control group design with dependent pretest and posttest samples. A total of 55 respondents aged 19-25 years were taken using purposive sampling. Respondents were divided into two groups: intervention I (physical activity and tele-nutrition counseling) and intervention II (physical activity). Food consumption data was taken by 2x24H recall interview. Data analysis used Paired Sample Test, Independent Sample Test, Wilcoxon, And Mann Whitney. Respondents with obesity I nutritional status were 49.05% and obesity II were 50.95%. There is a difference in dietary energy density in intervention I (p = 0.047). There is no difference in food nutrient density in intervention I (p = 0.480). There was no difference in dietary energy density (p = 0.548) and food nutrient density (p = 0.307) in intervention II. There was no difference in dietary energy density (p = 0.589) and food nutrient density (p = 0.134) between intervention I and intervention II after treatment. There was a difference in dietary energy density before and after treatment in intervention I. There was no difference in muscle mass and dietary density between intervention I and intervention II after treatment.